2017
DOI: 10.1038/s41598-017-10041-6
|View full text |Cite
|
Sign up to set email alerts
|

Zinc depletion promotes apoptosis-like death in drug-sensitive and antimony-resistance Leishmania donovani

Abstract: Micronutrients are essential for survival and growth for all the organisms including pathogens. In this manuscript, we report that zinc (Zn) chelator N,N,N’,N’-tetrakis(2-pyridinylmethyl)-1,2-ethylenediamine (TPEN) affects growth and viability of intracellular pathogen Leishmania donovani (LD) by a concentration and time dependent manner. Simultaneous addition of zinc salt reverses the effect of TPEN. Further experiments provide evidence of apoptosis-like death of the parasite due to Zn-depletion. TPEN treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…LD (MHOM\IN\1983\AG83) was used for all experiments. Culture and maintenance of the virulent parasites by passaging through Balb/ c mice were performed as described before (Das et al, 2009;Saini, Bharati, Shaha, & Mukhopadhyay, 2017). Freshly transformed promastigotes were maintained in M199 medium supplemented with 10% FBS, 100 units/ml penicillin, 100 μg/ml streptomycin at 22°C.…”
Section: Parasite Culturementioning
confidence: 99%
“…LD (MHOM\IN\1983\AG83) was used for all experiments. Culture and maintenance of the virulent parasites by passaging through Balb/ c mice were performed as described before (Das et al, 2009;Saini, Bharati, Shaha, & Mukhopadhyay, 2017). Freshly transformed promastigotes were maintained in M199 medium supplemented with 10% FBS, 100 units/ml penicillin, 100 μg/ml streptomycin at 22°C.…”
Section: Parasite Culturementioning
confidence: 99%
“…Additionally, the ontology enrichment analysis revealed that most genes with CNVs were involved in cellular ion zinc homeostasis in many clinical isolates; some of these genes were previously identified in L. infantum [63], as reported by a previous study, wherein the authors have described the need of these genes in the parasite to maintain the intracellular concentrations of zinc and avoid the toxic effects of this metal. Considering the aforementioned findings, we believe that L. panamensis, similar to other Leishmania species, needs to maintain intracellular zinc homeostasis because of the importance of this metal as a cofactor of several hundred proteins involved in replication, infectivity, and virulence [64,65]. Another group of genes with CNVs observed in some genomes was associated with glycerol transport.…”
Section: Discussionmentioning
confidence: 95%
“…TPEN has been used as a zinc chelator in several studies [15][16][17]. Therefore, we tested the effect of zinc on biofilm formation by T. asahii.…”
Section: Resultsmentioning
confidence: 99%